Biodiesel production from municipal secondary sludge. (September 2016) - Kumar, Manish; Ghosh, Pooja; Khosla, Khushboo; Thakur, Indu Shekhar
Highlights: Municipal secondary sludge was found to be an ideal feedstock for biodiesel. Optimization by Response surface methodology enhanced the biodiesel yield. Biodiesel yield under optimum conditions was 20.76 ± 0.04% of sludge solids. Analysis of FAME profile revealed a good quality biodiesel. Abstract: In the present study, feasibility of biodiesel production from freeze dried sewage sludge was studied and its yield was enhanced by optimization of the in situ transesterification conditions (temperature, catalyst and concentration of sludge solids). Optimized conditions (45 °C, 5% catalyst and 0.16 g/mL sludge solids) resulted in a 20.76 ± 0.04% biodiesel yield. The purity of biodiesel was ascertained by GC–MS, FT-IR and NMR ( 1 H and 13 C) spectroscopy. The biodiesel profile obtained revealed the predominance of methyl esters of fatty acids such as oleic, palmitic, myristic, stearic, lauric, palmitoleic and linoleic acids indicating potential use of sludge as a biodiesel feedstock.